Generation Z’s expectations from coaching - AlZankanh, Ahmed Jihad MohammedAmen; Alizadeh Sani, Mohsen; Shirkhodaie, Meysam; Safari, Mohammad; Hosseini, Aboalhasan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
This study examines the expectations and motivations of Generation Z students toward life coaching, highlighting the growing importance of understanding how this cohort interacts with life coaching. Employing an applied qualitative design within an interpretive paradigm, the research drew on semi-structured interviews with 20 students from the University of Kirkuk, Iraq. Data were analyzed thematically, following systematic coding procedures until theoretical saturation was reached. The findings revealed seventeen shaping students’ expectations from coaching: Coaching Approach (personalized guidance), Communication Skills (active listening, constructive feedback, effective communication), Goal Orientation (measurable goals, transparent evaluation), Skill Development (enhancing capabilities, expertise transfer), Emotional Support (motivation, empathy, psychological safety), Professional Attitude (ethics, accountability, flexibility), Problem-Solving Capacity (practical decision-making skills), and Resource Facilitation (access to tools and networks). The study contributes to the literature on coaching and generational learning by highlighting the culturally grounded expectations of Iraqi students. Practically, the findings suggest that coaches and educational institutions should adopt tailored, ethically sound, and goal-focused approaches to enhance engagement and effectiveness when working with Generation Z.